STRATEGI DAKWAH SUFISTIK PETANI (STUDI DAKWAH LEMBAGA PENGKAJIAN AL-MAUNAH AL-KAROMAH) TERHADAP MASYARAKAT DUSUN TANJUNG GUNDUL DESA KARIMUNTING KECAMATAN SUNGAI RAYA KEPULAUAN KABUPATEN BENGKAYANG - Wahyu Kusuma Dewi; Zulkifli Zulkifli (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2020)
The majority of the population who live in the village area work as farmers. Some farmers spend their time in the fields. So, Most farmers find it difficult to worship, especially to praying together in mosques. But, in Tanjung Gundul there is a group of devount people who worship like always praying together in mosque even thought they are a farmers. It turns out they are members of a study institute of Al-Maunah Al-Karomah (Al-Makka). Besides that, they also regularly attend recitation from Al-Makka. It’s show that the strategy of preaching by the Al-Makka to farmers was effective. Therefore this study aims to reveal what strategies are used by da’i from Al-Makka. This research in included in qualitative research. This research method uses a case study. Data collection techniques using interviews, observation, and documentation with data collection tools in the form of researchers themselves, interview guidelines and observation guidelines. Data analysis using data reduction, data presentation and data verification. Data validity test using triangulation and peer deriefing. Based on the analysis carried out, the researcher can conclude that: the sufistic da’wah strategy of farmers implemented by da’’ from Al-Makka, namely da’wah is carried out in the al-hikmah way which adapts to mad’u habits. The majority of mad’u work as farmers, most of time spent on agricultural land. Therefore da’i Al-Makka took this into account by guiding mad’u as well as in agriculture. From an economic-social point of view, it runs smoothly, then the next is from a spritual perspective. Dai made an approach using a sufistic da’wah stategy through the practice of the tarekat teachings ti the peasants. It turns out that non-forcing strategy is in great demand for mad’u.